Cost-Effectiveness Analysis of Long-acting Injectable Once-monthly of Aripiprazole Compared with Long-acting Injectable Once-monthly Paliperidone Palmitate for the Treatment of Stable Schizophrenia Patients in Thailand - Ueapanjasin, Piyanut; Thavornwattanayong, Wiwat; Lertsirimunkong, Jadesada; Chaiyakittisopon, Kamolpat (Siriraj Medical Journal, 2023)
Objective: Long-acting injectable (LAI)-aripiprazole and LAI-paliperidone palmitate are both second-generation antipsychotics that have been introduced to increase drug compliance in patients. These attributes are expected to enhance drug compliance, particularly in stable patients. The previous studies demonstrated that the efficacy of LAI-aripiprazole and LAI-paliperidone palmitate is controversial. Nevertheless, the costs of treatments and adverse events of both LAI-aripiprazole and LAI-paliperidone palmitate are unlikeness. As there had been no previous cost-effectiveness studies comparing the use of LAI-aripiprazole and LAI-paliperidone palmitate in Thailand, this study was carried out to investigate the matter. Materials and Methods: This study analysed the cost-effectiveness of LAI-aripiprazole compared with LAI-paliperidone palmitate in the treatment of stable schizophrenia, by using the Markov model from a societal perspective. Results: The total cost of treatment with LAI-aripiprazole and LAI-paliperidone palmitate was 1,334,919.05 baht and 1,329,818.79 baht, respectively, while the quality-adjusted life years (QALYs) were both 16.35 years. Life-year of the treatment with LAI-aripiprazole and LAI-paliperidone was 24.27 years and 24.25 years, respectively. The cost-effectiveness ratios (CER) of the treatment with LAI-aripiprazole and LAI-paliperidone palmitate were 81,652.85 baht/QALY gained and 81,330.94 baht/QALY gained, respectively. Conclusion: In Thailand, the treatment of stable schizophrenia with LAI-aripiprazole was shown to provide similar benefits to LAI-paliperidone palmitate in terms of QALYs, despite being more costly. Comparatively, LAI-aripiprazole exhibited better clinical efficacy and led to a longer average life expectancy than LAI-paliperidone. Treatment with LAI-aripiprazole may be dominant strategy, especially with a 2% reduction in drug cost. The results could contribute to appropriate decision-making by policymakers.